2020
DOI: 10.3389/fonc.2020.01078
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transcriptional Factor Brachyury on Cell Cycle Regulation in Non-small Cell Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related death, and non-small cell lung cancer (NSCLC) accounts for almost 80-85% of all lung cancer cases. The transcriptional factor brachyury has been verified to promote tumor cells migrate, invade, and metastasis in various types of tumors, whereas divergent roles of brachyury on cell proliferation have been reported in several types of tumor cells. In this study, we attempted to explore the effect of brachyury on the cell cycle progression and proliferation capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The T-box protein Brachyury is a transcription factor that is widely expressed in multiple solid tumors and is associated with tumor aggressiveness and poor patient prognosis [ 25 ]. Our previous study has demonstrated that Brachyury and downstream target genes together involve in lung cancer cell cycle regulation by inducing accelerated transition through G2/M, promoting tumor cell proliferation and inhibiting apoptosis [ 15 ]. In addition, Brachyury has been proven to play an important role in promoting breast cancer cell progression [ 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T-box protein Brachyury is a transcription factor that is widely expressed in multiple solid tumors and is associated with tumor aggressiveness and poor patient prognosis [ 25 ]. Our previous study has demonstrated that Brachyury and downstream target genes together involve in lung cancer cell cycle regulation by inducing accelerated transition through G2/M, promoting tumor cell proliferation and inhibiting apoptosis [ 15 ]. In addition, Brachyury has been proven to play an important role in promoting breast cancer cell progression [ 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have reported that Brachyury is expressed in mesodermal precursor cells, gradually downregulated during latestage embryos and is eventually undetectable in the majority of normal adulthood tissues [12]. More recently, Brachyury was described to be aberrantly overexpressed in several tumors, including lung [13][14][15], breast [11], prostate [16], colon [17], and testicular [18] cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the SOC + immunotherapy regimen yielded biological activity in the form of substantial increases in multifunctional CD4+ and CD8+ T cells specific for the cascade antigens MUC1 and brachyury. Among them, the MUC1 and Brachyury pathways play important roles in cancer development and immune evasion and have become potential targets for tumor immunotherapy ( 202 , 203 ).…”
Section: Preclinical and Clinical Studies Of Inducing Chemotherapy Co...mentioning
confidence: 99%
“…Transcription factor Brachyury, a protein of 435 amino acids, binds with the canonical T-domain DNA sequence: TCACACCT. Brachyury regulates posterior mesoderm formation and notochord differentiation by directly activating downstream mesoderm-specific genes (Chen et al, 2020a;Chen et al, 2020b;Xu et al, 2020). The embryonic notochord is considered to be the developmental origin of mature adult NP tissue (Richardson et al, 2017).…”
Section: Main Textmentioning
confidence: 99%